2017
DOI: 10.1007/s10531-017-1291-2
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA barcode to relate landscape attributes to small vertebrate roadkill

Abstract: Large vertebrates are the main focus of roadkill studies because their greater size facilitates taxonomic identification and the collection of statistical data. However, these studies fail to effectively include and identify small vertebrates and correlate roadkill events with the surrounding landscape. Here we showed the effectiveness of molecular data to identify small vertebrate roadkill, and we correlated landscape structure attributes with the location of roadkill for functional groups of varying mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…First geographic records (FGR) and new roadkill records (NRR) for reptile and bird species were verified from the literature. We compared our dataset to data collected by De Souza et al (2014) from the same highway (BR-262) and data of road-killed reptiles and birds from other Brazilian roads (Novelli et al 1988, Prado et al 2006, Silva et al 2007, Coelho et al 2008, Hengemühle and Cademartori 2008, Cunha et al 2010, Hartmann et al 2011, Ramos et al 2011, Santana 2012, Santos et al 2012, 2014Carvalho et al 2014, Klippel et al 2015, Machado et al 2015, Almeida et al 2016, Braz and França 2016, Deffaci et al 2016, Saranholi et al 2016, Steil et al 2016, Corrêa et al 2017, Miranda et al 2017, Rodríguez-Castro et al 2017, Viturino and Graciolli 2017, Gonçalves et al 2018, Ramos-Abrantes et al 2018.…”
Section: Methodsmentioning
confidence: 99%
“…First geographic records (FGR) and new roadkill records (NRR) for reptile and bird species were verified from the literature. We compared our dataset to data collected by De Souza et al (2014) from the same highway (BR-262) and data of road-killed reptiles and birds from other Brazilian roads (Novelli et al 1988, Prado et al 2006, Silva et al 2007, Coelho et al 2008, Hengemühle and Cademartori 2008, Cunha et al 2010, Hartmann et al 2011, Ramos et al 2011, Santana 2012, Santos et al 2012, 2014Carvalho et al 2014, Klippel et al 2015, Machado et al 2015, Almeida et al 2016, Braz and França 2016, Deffaci et al 2016, Saranholi et al 2016, Steil et al 2016, Corrêa et al 2017, Miranda et al 2017, Rodríguez-Castro et al 2017, Viturino and Graciolli 2017, Gonçalves et al 2018, Ramos-Abrantes et al 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal differences in mortality rate were also observed for tropical bird species in two federal highways in Southern Brazil (Alvez da Rosa & Bager, 2012). In addition, the spatial configurations and attributes of roads within landscapes and their distance to wildlife habitats may influence the rate at which animals are killed (Glista, DeVault, & DeWoody, 2008;Fahrig & Rytwinski 2009;Rodríguez-Castro et al, 2017). Thus, roads in close proximity to natural habitats are expected to have greater impacts on wildlife than those located away from natural habitats.…”
Section: Introductionmentioning
confidence: 97%
“…However, González-Gallina, Benítez-Badillo, Rojas-Soto and Hidalgo-Mihart (2013) found that mammals were the most frequently killed on roads in grassland in Mexico, and that 95 % of the 827 mammals found were small rodents. In addition, accurate accounts and precise identification of small bodies were achieved recently using DNA barcoding in Brazil (Rodríguez-Castro, Ciocheti, Ribeiro, Ribeiro, & Galetti Jr., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations